The SWOT AHP Analysis of Mitra Utama Kepabeanan Policy in Directorate General of Customs and Excise - Destiko Teguh Rinaldi; Mudiyati Rahmatunnisa; Arianis Chan (Department of Public Administration, 2022)
The Mitra Utama (MITA) Kepabeanan Policy implemented in the Directorate General of Customs and Excise aims to reduce logistics costs in order to improve Indonesia's economic competitiveness, as well as give appreciation to compliant importers and exporters. However, the implementation of the policy has not been optimal because of the high logistics costs, and lagging ranking of Indonesia's Logistic Performance Index in the Southeast Asia region, as well as policies that have not been able to reduce the overall dwell time for imported goods. Recommendations for improving policy performance will be drawn up using a mixed method of exploratory sequential models. Qualitative data collection techniques are carried out through literature studies, observations, interviews, while quantitative data collected through questionnaire filling. Qualitative data analysis uses a hierarchical linear approach, while quantitative data analysis uses a combined method of SWOT and AHP. Policy recommendations will be selected based on the highest-score strategy. Based on the results of the study, the strength factor is considered the most important thing of this policy. The main recommendation is encouraging the integration of risks between government agencies involved in the import and export process.